Prezentacja wariantów akcentuacyjnych w nowoczesnym rosyjsko-polskim słowniku przekładowym - Gasek, Bogumił (Przegląd Rusycystyczny, 2017)
Презентация акцентных вариантов в современном русско-польском переводном словаре В настоящей статье была предпринята попытка сформулировать принципы презентации акцентных вариантов в современном русско-польском переводном онлайн-словаре. Отправной точкой для реализации этой цели послужил анализ информации о вариантах ударения в Большом русско-польском словаре под редакцией Яна Вавжинчика в сопоставлении с данными самых больших и авторитетных орфоэпических словарей русского языка. Presentation of the word stress variations in the contemporary translation Russian-Polish on-line dictionary The present paper attempts to formulate principles of presenting the word stress variations in the contemporary translation Russian-Polish on-line dictionary on the basis of the comparative analysis that was conducted on the resources of The Great Russian-Polish Dictionary edited by Polish Scientific Publishers "PWN" as well as on data entries from the most authoritative orthoepic dictionaries of contemporary Russian. key words: lexicographical criticism, translation Russian-Polish dictionary, on-line dictionary, word-stress variation.